Liver Immunology, Immunotherapy, and Liver Cancers: Time for a Rethink? - Carroll, Hailey K.; Duffy, Austin G.; O'Farrelly, Cliona (Seminars in Liver Disease, 2022)
The complex immune system of the liver has a major role in tumor surveillance, but also partly explains why current immune therapies are poorly effective against liver cancers. Known primarily for its tolerogenic capacity, the hepatic immune repertoire also comprises diverse populations of armored immune cells with tumor surveillant roles. In healthy people, these work together to successfully identify malignant cells and prevent their proliferation, thus halting tumor formation. When frontline hepatic immune surveillance systems fail, compromised hepatic immunity, driven by obesity, infection, or other pathological factors, allows primary or secondary liver cancers to develop. Tumor growth promotes the normal tolerogenic immunological milieu of the liver, perhaps explaining why current immunotherapies fail to work. This review explores the complex local liver immune system with the hope of identifying potential therapeutic targets needed to best overcome immunological barriers in the liver to create an environment no longer hostile to immunotherapy for the treatment of liver cancer.
Keywords: liver immunology; hepatocellular carcinoma; NK cells; liver cancer; immunotherapy